Analysis of Unemployment and Poverty Rates in Central Kalimantan Province 2003-2008 - Ana Mustaka (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
This study aims to analyze: Unemployment and poverty rates affect the Regional Revenue and Expenditure Budget, Economic Growth and Regional Minimum Wages in Central Kalimantan Province. This research is a quantitative descriptive research. The data used is secondary time series data for 2001-2018. Collecting data using library research method. Data analysis using Multiple Linear Regression model. The results of the study indicate that the unemployment rate in Central Kalimantan Province has a direct negative and significant effect on the Regional Revenue and Expenditure Budget and Economic Growth, but has a positive effect on the Regional Minimum Wage. Likewise, the Poverty Level in Central Kalimantan Province directly has a negative effect on the Regional Revenue and Expenditure Budget, Economic Growth and Regional Minimum Wages in Central Kalimantan Province.